Identification and Control of Occupational Safety and Health Risks (K3): A Case Study of The Basarnas K.N. Pacitan 102 Ship in Kendari City - Ruslan Ruslan; Dwiprayogo Wibowo; Wa Ndibale; Ilham Ilham; Moch. Assiddieq; Aryani Adami (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2025)
Identification and control of occupational safety and health (OSH) risks on the BASARNAS ship K.N. Pacitan 102, Kendari City, are very important to identify factors that can potentially cause occupational accidents. This study used qualitative methods to characterize the forms of potential hazards and risk control, using observation methods in the K.N. Pacitan 102 ship's room environment, and to assess the risk level of the infrastructure and hazards (safety signs) on the ship. Based on the observation, there is a high risk in the galley room of being struck by glass cutlery or burned by cooking utensils. Moderate risks are partially identified in the wheelhouse area, radio equipment, corridor, gallery room, passenger room, kitchen, mosque, and engine room with risk descriptions in the form of high temperatures (heat), hearing loss, injuries due to collisions, the presence of fragments of iron & glass materials, saturation from a narrow work environment and lack of air circulation. At the same time, low risks are also found in some wheelhouse rooms, radio equipment, corridors, meeting rooms, hospitals, offices, and engine rooms, with risk descriptions such as bumping, slipping, saturation in work positions, and a lack of space for movement. Risk control is grouped into four sub-risk controls, such as substitution, engineering/isolation, elimination, and administration/training/ preparation of personal protective equipment (PPE). This study has had an impact on the readiness of BASARNAS to continue to improve the readiness and completeness of work safety to minimize all opportunities for work accidents that can occur at any time on the BASARNAS Ship K.N. Pacitan 102.